Determinants of Strategy Agility and Performance of Micro, Small and Medium Enterprises Halal Industry - Helmalia, Helmalia; Masdupi, Erni; Rasyid, Rosyeni (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2025)
The growing halal industrial food and beverage business has not yet reflected competitive performance. Micro, small and medium enterprises in this sector often face challenges in the form of operational efficiency and low financial literacy, thus affecting their competitiveness. This study aims to analyze the effect of agility strategies on the performance of micro, small and medium enterprises in the halal industry. This research uses a quantitative approach through a survey with simple linear regression data analysis techniques. The object of research is halal-certified micro, small and medium enterprises, with data obtained from the Ministry of Religious Affairs, the Ministry of Cooperatives and micro, small and medium enterprises, the Central Bureau of Statistics, and the Ministry of Tourism and Creative Economy. The results show that the agility strategy allows micro, small and medium enterprises to operate more flexibly and responsively to market changes and meet strict halal standards. These findings form the basis for micro, small and medium enterprises in improving operational efficiency in order to strengthen the competitiveness of micro, small and medium enterprises in local and global markets. With the ability to adapt and innovate quickly according to the needs of the halal industry market in Indonesia.